Survival time and search time in water: Past, present and future. (December 2022) - Tipton, Michael; McCormack, Elizabeth; Elliott, Graham; Cisternelli, Monica; Allen, Arthur; Turner, Arden C.
Abstract: The prediction of survival time for those immersed in water remains a key element in the function of search and rescue organisations around the globe. The data on which such predictions are made come from laboratory studies and actual incidents. The UK National Immersion Incident Survey (UKNIIS) represents one of the largest surveys undertaken in this area. The UKNIIS data are obtained by questionnaire from immersion incidents around the British Isles. The survey has been in operation since 1991 and at the time of writing contained almost 1600 cases. The aim of the present work was to analyse these cases with the aim of establishing a model for the prediction of survival time in water. This analysis is described in this paper: two model approaches are presented and their strengths and weaknesses are discussed. Recommendations for the use and development of such models are made. Highlights: This paper provides new data on the key variables for predicting survival time in water. It provides the original data, and describes the process from which and by which the IAMSAR (IMO) guidelines for search and rescue were established. It provides recommendations for refining these guidelines.